Konsonan dalam Bahasa Koloncucu - Fida Febriningsih (Kantor Bahasa Provinsi Maluku Utara, 2017)
Koloncucu language is one of the regional languages ​​in North Maluku belonging to the category of extinct languages ​​(moribund languages), because it has a very small number of speakers. Within a few decades, this language will completely disappear with the speaker. Scientific data on this language has not been done. This paper aims to describe the form and classification of consonants in Koloncucu language, as one of the efforts to preserve local languages. This research uses descriptive method with three stages, namely data supply stage, data analysis phase, and presentation stage of data analysis. Data analysis is done after the data classification process is then applied using the agih method with the technique for the direct element. The results of this paper are the form and classification of consonants in Koloncucu language, namely: the consonant of the larup (Stops, Plosives), nasal consonants (Nasals), side consonants (Laterals), fricative, fristions consonants, vibrating consonants (Trills, Vibrants), and semi vocals. While the touch consonants (Tap), strong touch consonants (Flap), and consonant alloys (Affricates) are not found in Koloncucu.